Analisis Kegagalan Boom Crane dan Pencegahannya - Elvis Adril -; Nasirwan - -; Tri Wibowo -; Julnaidi - - (Jurnal Ilmiah Poli Rekayasa, 2014)
Sleeve (Boom) on Crawler Crane is the main equipment that serves the weight at the time of appointment (Hoisting).The problem which is founded is a fracture at the boom while lift 6 Tons of weight while the optimum design of equipment is 50 tons. The aim of this research is to found the root cause of the fracture by using photo documentation fractografi (microfractografi and macrofractografi), and hardness tests, and test the chemical composition at the surface faults boom crane. We used Finite element method (FEM) to form simulated load. The results is that the porblem accured because of error while read the load chart and error in SOP